A hydrodemetallization catalyst, its preparation method and use
Patent Information
- Application Number
- CN202510570089.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
上述方法制得的加氢脱金属催化剂活性和稳定性仍有待进一步提升
[0085]本发明提供了一种加氢脱金属催化剂的制备方法,采用两次浸渍的方式引入活性金属,为进一步减弱第一活性金属(比如镍)和干燥物粉体在研磨、混捏过程中产生的相互作用,首先,将第一活性金属(比如镍)以浸渍的形式负载在活性炭之上,在此过程中引入了分散助剂,防止含有第一活性金属的活性炭在焙烧过程中金属发生聚集,让金属在活性炭上先行均匀分布。其次,研磨过程中,在活性炭上引入的碱性助剂会在混捏成型过程中形成“保护膜”,减少第一活性金属(比如镍)与氧化铝之间的相互作用。而后,在得到复合载体上进行覆碳膜处理,碳膜形成后可保证后续第二活性金属中的主活性金属钼浸渍过程中不与助活性金属镍及载体接触,主活性金属钼可均匀分散在碳膜之上。最后,混合气氛焙烧下,空气除去碳膜,主活性金属钼则均匀分散在载体之上。第一次浸渍的目的是通过控制催化剂中第一活性金属镍的含量来有效地控制催化剂表面的酸性,第二次浸渍的目的是进一步调控催化剂表面的加氢活性。本发明分两次引入了活性金属,不仅调控了催化剂表面的酸性,还进一步控制了催化剂的加氢活性;有效地调控了催化剂表面的活性位点;在提高催化剂整体性能的同时,有利于延长装置的运转周期。该方法不仅可以进一步减弱金属与载体之间的相互作用,还可有效避免因两种金属混合浸渍时在载体表面竞争吸附而导致活性金属分布不均匀的问题。此外,在复合载体上进行覆碳处理,并通过惰性气体焙烧,水分逐渐蒸发,乳胶颗粒逐渐挤压形成薄膜,且结构中含有可交联基团,交联形成立体网状薄膜,该薄膜临时为第二活性金属提供负载位置,待催化剂焙烧后,该薄膜消失,第二活性金属则均匀分散至载体上,并与第一活性金属相配合,通过各步骤相互配合,提高加氢脱金属的活性和稳定性。
Smart Images

Figure BDA0005386944080000151 
Figure BDA0005386944080000152 
Figure BDA0005386944080000161
Abstract
Description
Technical Field
[0001] This invention relates to a hydrogenation catalyst, specifically to a hydrogenation demetallization catalyst suitable for the hydrotreating process of residual oil, its preparation method, and its application. Background Technology
[0002] In recent years, crude oil resources have become increasingly scarce, and the trend of heavy and inferior crude oil has intensified. Many refineries are adapting to economic development and seeking effective methods to convert heavy oil into lighter products. Hydrotreating technology, as an important route for converting heavy oil into lighter products, also faces new challenges and problems under the current circumstances. Residue hydrotreating technology is a crucial means of converting heavy oil into lighter products in the petroleum refining process, and its development hinges on the research and development of catalysts with good activity and stability. Hydrodemetallization catalysts, positioned before hydrodesulfurization and decarbonization agents, play a vital role in removing various metallic impurities (mainly Ni and V) from the feedstock, thus ensuring the overall effectiveness of the hydrotreating process. Therefore, developing hydrodemetallization catalysts with suitable activity and good stability is particularly important.
[0003] CN105709765A discloses a method for preparing a hydrodemetallization catalyst for residual oil, comprising the following steps: (1) mixing a pore-expanding agent, boehmite dry powder, extrusion aid, and adhesive solvent into a plastic body, extruding and drying; (2) unsaturatedly spraying the dried support from step (1) with a mixed solution of phosphoric acid and ammonium oxalate, subjecting the impregnated support to sealed heating treatment, with the treatment pressure being the self-generated pressure under sealed conditions, the treatment temperature being 120–160℃, and the treatment time being 6–12 hours, and the treated support being dried and calcined to obtain an alumina support; (3) impregnating the alumina prepared in step (2) with the active component, and then drying and calcining to obtain an alumina support for the hydrodemetallization catalyst of residual oil. The activity and stability of the hydrodemetallization catalyst prepared by the above method still need to be further improved. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a hydrodemetallization catalyst, its preparation method, and its application. This catalyst, used in the hydrodemetallization process of residue oil, exhibits high hydrodemetallization activity and metal-containing capacity, ensuring long-term operation of the equipment.
[0005] The first aspect of this invention provides a method for preparing a hydrogenation demetallization catalyst, comprising the following steps:
[0006] (1) Preparation of activated carbon carrier modified with first active metal;
[0007] (2) The activated carbon carrier modified with the first active metal obtained in step (1) is mixed with boehmite and adhesive, molded, and calcined to obtain a composite carrier.
[0008] (3) The composite carrier obtained in step (2) is subjected to surface carbon coating treatment and calcined to obtain the modified composite carrier.
[0009] (4) The modified composite support obtained in step (3) is impregnated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal, and then calcined to obtain the hydrogenation demetallization catalyst.
[0010] Further, in step (1), the preparation method of the first active metal modified activated carbon support includes:
[0011] (I) Activated carbon is impregnated with a first active metal impregnation solution containing a dispersing aid and then calcined to obtain a first active metal modified activated carbon precursor;
[0012] (II) The first active metal modified activated carbon precursor obtained in step (I) is mixed with an alkaline additive, ground and dried to obtain the first active metal modified activated carbon carrier.
[0013] Further, in step (I), the dispersing agent is silica sol. The silica sol contains 20.0% to 50.0% silica by mass.
[0014] Further, in step (I), the first active metal is at least one of Group VIII metals, preferably Ni and / or Co, the nickel source is selected from at least one of basic nickel carbonate, nickel nitrate, and nickel sulfate, and the cobalt source is preferably cobalt nitrate. Further, in the first active metal impregnation solution containing the dispersing aid, the mass content of the first active metal, calculated as oxide, is 2.0% to 8.0%, and the mass content of the dispersing aid, calculated as silica, is 2.0% to 6.0%.
[0015] Further, in step (I), the activated carbon is high-temperature activated carbon. The minimum heat resistance temperature of the high-temperature activated carbon is 750°C. The particle size of the activated carbon is 0.1–6.0 μm.
[0016] Furthermore, in step (I), the impregnation method is saturated impregnation.
[0017] Further, in step (I), after impregnation, the carbon is dried and calcined to obtain the first active metal-modified activated carbon precursor. The drying conditions are: temperature of 120–180°C and drying time of 4–8 h. The calcination conditions are: temperature of 550–750°C and time of 3–8 h, and the calcination atmosphere is one or more of air, water vapor, and nitrogen.
[0018] Furthermore, in step (I), the first active metal (e.g., Ni) is a co-active metal, which can interact with the support during the calcination process to weaken the acidity of the support, and can also synergize with the main active metal (e.g., Mo) in the second active metal component, which is beneficial to the hydrogenation reaction.
[0019] Furthermore, in step (II), the alkaline auxiliary agent is one or more of alkaline compounds such as sodium hydroxide, potassium hydroxide, and sodium carboxylate (e.g., sodium acetate, sodium formate).
[0020] Further, in step (II), the mass ratio of the alkaline additive to the activated carbon used in step (I) is 0.01 to 0.10, for example, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, etc., and any value within the range formed by any two of these values.
[0021] Furthermore, in step (II), the grinding can be carried out by ball milling, sand milling, or other methods. The ground material not only has a more uniform metal dispersion, but the alkaline additive will also form a "first protective film" on the surface of the dried material during the molding process in step (2). After grinding, a ground sample with an average particle size of 2.0 to 8.0 μm is obtained.
[0022] Further, in step (II), the drying conditions are: temperature of 120-180℃ and drying time of 4-8h.
[0023] Furthermore, in step (2), the boehmite is obtained by conventional methods, such as the aluminum sulfate method, aluminum alkoxide method, sol-gel method, etc. The alumina content in the boehmite is 65.0% to 80.0% by mass.
[0024] Further, in step (2), the adhesive can be an inorganic acid and / or an organic acid. The inorganic acid can be one or more of nitric acid, sulfuric acid, boric acid, and phosphoric acid, and the organic acid can be one or more of tartaric acid, citric acid, and oxalic acid.
[0025] Further, in step (2), the mass of the adhesive is 0.5% to 5.0% of the total mass of the pseudoboehmite (calculated as alumina) and the activated carbon carrier modified with the first active metal.
[0026] Furthermore, in step (2), the forming method can be at least one of extrusion, sheeting, and ball forming. The formed shape can be clover-shaped, four-leaf clover-shaped, butterfly-shaped, cylindrical, spherical, or strip-shaped, etc.
[0027] Further, in step (2), molding aids, such as at least one of extrusion aids and deionized water, can be added during the molding process according to molding requirements. The extrusion aid can be one or more of methylcellulose, ethylcellulose, guar gum, and starch. The mass of the extrusion aid added is 0.5% to 8.0% of the total mass of boehmite (calculated as alumina) and modified activated carbon B. The amount of deionized water used can be 80% to 120% of the total mass of boehmite (calculated as alumina) and modified activated carbon B.
[0028] Further, in step (2), after molding, the composite carrier is dried and calcined to obtain a composite carrier. The drying temperature is 120-200℃, and the drying time is 2-12h.
[0029] Further, in step (2), the calcination process employs programmed temperature increase at a rate of 1℃ / min to 3℃ / min. The calcination temperature is 550℃ to 750℃, the calcination time is 2 to 8 hours, and the calcination atmosphere is one or more of air, nitrogen, or water vapor, preferably air.
[0030] Further, in step (3), the carbon coating treatment preferably uses an aqueous emulsion containing a polymer compound and water-soluble cellulose. In the aqueous emulsion, the polymer compound has a mass content of 8.0% to 16.0%, and the water-soluble cellulose has a mass content of 0.5% to 3.5%.
[0031] Furthermore, the polymer compound is not particularly limited and can be selected from one or more of polyimide, polyfurfuryl alcohol, and phenolic resin. The water-soluble cellulose is one or more of hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose. The ratio of the aqueous emulsion (by volume mL) to the composite carrier (by mass g) is 0.8–1.5 mL / g.
[0032] Further, in step (3), after the carbon coating treatment is completed, the modified composite carrier is obtained by drying and calcination. The drying conditions are: drying temperature of 120-200℃ and drying time of 2.0-12.0h. The calcination conditions are: calcination temperature of 500-700℃ and calcination time of 2.0-8.0h, and the calcination atmosphere is an inert atmosphere, which is one or more of nitrogen and argon.
[0033] Furthermore, in step (4), the impregnation method is saturated impregnation.
[0034] Further, in step (4), the modified composite carrier is placed in the impregnation solution and left to stand for 24–48 hours, then dried and calcined to obtain the catalyst. The drying temperature is 120–200°C, and the drying time is 2–12 hours. The calcination adopts a two-stage calcination process. The first stage calcination temperature is 350–450°C, the calcination time is 2–6 hours, and the calcination atmosphere is one or more of air, nitrogen, or water vapor, preferably air. The second stage calcination temperature is 450–750°C, the calcination time is 2–8 hours, and the calcination atmosphere is one or more of air, nitrogen, or water vapor, preferably nitrogen. The second stage calcination temperature is 150–250°C higher than the first stage calcination temperature.
[0035] Further, in step (4), the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal includes at least one group VIB metal and at least one group VIII metal; further, the impregnation solution includes an inner aqueous phase, an oil phase coating the inner aqueous phase, and an outer aqueous phase, wherein the inner aqueous phase includes a group VIB metal source, a co-emulsifier, a water-soluble polymer, water, and an optional auxiliary agent source, and the outer aqueous phase includes a group VIII metal source, a hydrophilic agent, and water; and the oil phase includes a surfactant and oil.
[0036] Further, the mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0, and more preferably 1.0:4.0 to 10.0, for example 1.0:4.0, 1.0:4.5, 1.0:5.0, 1.0:5.5, 1.0:6.0, 1.0:6.5, 1.0:7.0, 1.0:7.5, 1.0:8.0, 1.0:8.5, 1.0:9.0, 1.0:9.5, 1.0:10.0, etc., and any value within the range formed by any two of these values.
[0037] Furthermore, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, 9.0:1.0, etc., and any value within the range formed by any two of these values.
[0038] Furthermore, the mass ratio of the "internal aqueous phase / oil phase" to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, etc., and any value within any range formed by any two of these values. The mass of the "internal aqueous phase / oil phase" refers to the total mass of the internal aqueous phase and the oil phase coating the internal aqueous phase.
[0039] Furthermore, the water-soluble polymer is one or more of polyvinyl alcohol (molecular weight 170,000 to 220,000), carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate (molecular weight less than 10,000).
[0040] Furthermore, in the internal aqueous phase, the mass concentration of the water-soluble polymer is 4.0% to 14.0%.
[0041] Furthermore, in the inner aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; in the outer aqueous phase, the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL.
[0042] Further, the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co. The Group VIB metal source is one or more of ammonium molybdate, ammonium metatungstate, and molybdenum oxide, and the Group VIII metal source is one or more of nickel nitrate, cobalt nitrate, etc.
[0043] Furthermore, in the internal aqueous phase, the additive is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus, and the phosphorus source is one or more of phosphoric acid, ammonium hydrogen phosphate, and ammonium dihydrogen phosphate. In the internal aqueous phase, the concentration of the additive, calculated as an oxide, is 0–12.0 g / 100 mL, preferably 0.5–12.0 g / 100 mL.
[0044] Further, the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, and glycerin. The mass concentration of the co-emulsifier in the internal aqueous phase is 0.5% to 5.0%.
[0045] Further, the hydrophilic agent is one or more selected from polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide. The mass concentration of the hydrophilic agent in the external aqueous phase is 4.0% to 15.0%.
[0046] Furthermore, the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc.
[0047] Furthermore, the oil is selected from at least one of silicone oil and vegetable oil, the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0048] Further, in step (4), the preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal includes:
[0049] (a) The surfactant and oil are mixed and heated to obtain the oil phase;
[0050] (b) Mix the co-emulsifier, the Group VIB metal source, water and optional auxiliary source, and heat to obtain a clear solution;
[0051] (c) Add a water-soluble polymer to the clear solution obtained in step (b) to obtain an internal aqueous phase;
[0052] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a) while the oil phase remains liquid during the dropwise addition. Simultaneously, stirring and shearing are performed to homogenize the mixture, resulting in an "aqueous phase / oil phase" emulsion.
[0053] (e) Mixing a Group VIII metal source with water containing a hydrophilic agent to obtain an external aqueous phase;
[0054] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0055] Further, in step (a), the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc., or one or more of these. The oil may be at least one of silicone oil and vegetable oil, wherein the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0056] Furthermore, in step (a), the heating is carried out to a temperature of 45–85°C to make the oil phase appear as a uniform liquid.
[0057] Further, in step (a), the mass ratio of the added surfactant to the mass of oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0.
[0058] Further, in step (a), the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, polyvinyl alcohol, and glycerin.
[0059] Further, in step (a), the amount of the co-emulsifier is 0.5% to 5.0% of the mass of the internal aqueous phase obtained in step (c).
[0060] Further, in step (b), the Group VIB metal is preferably Mo and / or W, the molybdenum source can be one or more of molybdenum oxide, ammonium tetramolybdate, ammonium heptamolybdate, etc., and the tungsten source can be ammonium metatungstate. The additive is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus, and the phosphorus source can be one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, etc.
[0061] Further, in step (b), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0062] Further, in step (b), the heating is carried out to a temperature of 90-120°C to ensure that the substances added in step (b) are mixed evenly until a clear solution is obtained.
[0063] Further, in step (c), the concentration of Group VIB metals as oxides in the internal aqueous phase is 8-80 g / 100 mL, preferably 10-60 g / 100 mL, and the concentration of additives as oxides is 0-12.0 g / 100 mL, preferably 0.5-12.0 g / 100 mL.
[0064] Further, in step (c), the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate.
[0065] Further, in step (d), the mass concentration of the water-soluble polymer in the aqueous phase obtained in step (d) is 4.0% to 14.0%.
[0066] Furthermore, in step (d), the oil phase is kept in a liquid state at a temperature of 45–85°C, and the stirring rate is 400–800 r / min.
[0067] Further, in step (d), the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0.
[0068] Further, in step (d), the stirring-shear homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a shear homogenization time of 3 to 8 min, and a temperature of 50 to 85°C.
[0069] Further, in step (e), the Group VIII metal is preferably Ni and / or Co, the nickel source is one or more of basic nickel carbonate, nickel nitrate, etc., and the cobalt source can be cobalt nitrate.
[0070] Further, in step (e), the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide.
[0071] Further, in step (e), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0072] Further, in step (e), the mass concentration of the hydrophilic agent in the external aqueous phase is 4.0% to 15.0%.
[0073] Further, in step (e), the concentration of Group VIII metals in the external aqueous phase, calculated as oxides, is 2 to 50 g / 100 mL, preferably 5 to 30 g / 100 mL.
[0074] Further, in step (e), the mass ratio of the "internal aqueous phase / oil phase" emulsion to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0.
[0075] A second aspect of the present invention provides a hydrogenation demetallization catalyst prepared by the preparation method described in the first aspect.
[0076] Furthermore, the catalyst includes a support containing a first active metal and a second active metal. The support containing the first active metal includes alumina, activated carbon, and the first active metal, wherein the mass ratio of alumina to activated carbon is 1.0 to 4.0:1, preferably 1.5 to 3.5:1.
[0077] Further, the first active metal is at least one of Group VIII metals, preferably Ni and / or Co. The second active metal includes at least one of Group VIB metals (primary active metal) and at least one of Group VIII metals (auxiliary active metal), wherein the Group VIB metal is preferably Mo and / or W, and the Group VIII metal is preferably Ni and / or Co.
[0078] Furthermore, based on catalyst mass, the content of Group VIB metal oxides is 12.0%–20.0%, and the content of Group VIII metal oxides is 2.0%–8.0%.
[0079] Furthermore, in the catalyst, the content of Group VIII metals in the first active metal, calculated as oxides, is 20.0% to 45.0% of the total Group VIII metals in the catalyst, calculated as oxides, and the content of Group VIII metals in the second active metal, calculated as oxides, is 55.0% to 80.0% of the total Group VIII metals in the catalyst, calculated as oxides.
[0080] Furthermore, the specific surface area of the catalyst is 150–180 m². 2 / g, with a pore volume of 0.70–0.95 mL / g; preferably, the catalyst has a specific surface area of 155–170 m² / g. 2 / g, with a pore volume of 0.75~0.90mL / g.
[0081] Furthermore, the catalyst also includes an auxiliary agent selected from at least one of phosphorus, silicon, or boron, preferably phosphorus. The auxiliary agent, based on the mass of the catalyst, comprises 2.0% to 5.0% by weight of oxides.
[0082] Furthermore, the catalyst also includes silicon dioxide, with the silicon dioxide content ranging from 0.5% to 2.5% based on the mass of the catalyst.
[0083] The third aspect of this invention provides the application of the above-mentioned catalyst in the hydrotreating of heavy oil and residual oil.
[0084] Compared with the prior art, the present invention has the following beneficial effects:
[0085] This invention provides a method for preparing a hydrodemetallization catalyst. The method involves introducing an active metal through a two-stage impregnation process. To further reduce the interaction between the first active metal (e.g., nickel) and the dried powder during grinding and mixing, firstly, the first active metal (e.g., nickel) is impregnated onto activated carbon. A dispersing agent is introduced during this process to prevent metal aggregation on the activated carbon containing the first active metal during calcination, ensuring uniform metal distribution on the activated carbon. Secondly, during grinding, an alkaline agent introduced onto the activated carbon forms a "protective film" during mixing and molding, reducing the interaction between the first active metal (e.g., nickel) and alumina. Then, a carbon film is applied to the resulting composite support. The carbon film ensures that the primary active metal molybdenum in the second active metal does not come into contact with the co-active metal nickel or the support during subsequent impregnation, allowing the primary active metal molybdenum to be uniformly dispersed on the carbon film. Finally, under a mixed atmosphere calcination, air removes the carbon film, leaving the primary active metal molybdenum uniformly dispersed on the support. The purpose of the first impregnation is to effectively control the acidity of the catalyst surface by controlling the content of the first active metal, nickel, in the catalyst. The purpose of the second impregnation is to further regulate the hydrogenation activity of the catalyst surface. This invention introduces the active metal in two stages, which not only regulates the acidity of the catalyst surface but also further controls the hydrogenation activity of the catalyst; effectively regulates the active sites on the catalyst surface; and improves the overall performance of the catalyst while extending the operating cycle of the device. This method can not only further weaken the interaction between the metal and the support but also effectively avoid the problem of uneven distribution of active metal caused by competitive adsorption on the support surface when the two metals are mixed and impregnated. In addition, carbon coating is performed on the composite support, and then calcined with an inert gas. The moisture gradually evaporates, and the latex particles are gradually extruded to form a film containing crosslinkable groups, forming a three-dimensional network film. This film temporarily provides loading sites for the second active metal. After the catalyst is calcined, the film disappears, and the second active metal is uniformly dispersed on the support and cooperates with the first active metal. Through the cooperation of each step, the activity and stability of hydrogenation demetallization are improved.
[0086] This invention provides an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal, which utilizes a surfactant to disperse two active metals in the inner and outer aqueous phases, respectively. The inner aqueous phase acts as a carrier for the first active metal (a Group VIB metal) dispersed in the oil phase, while the outer aqueous phase acts as a carrier for the second active metal (a Group VIII metal). This results in an impregnation solution where the active metals are dispersed in both the inner and outer aqueous phases via carrier matrices, hence the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution. This impregnation solution is then used to impregnate a catalyst support, allowing for the preparation of a catalyst with a more uniform distribution of active metals both inside and on the surface of the support. In the preparation process of the impregnation solution, firstly, a co-emulsifier is used to fully disperse the first active metal in ionic form within the inner aqueous phase, resulting in an inner aqueous phase containing the first active metal. To control particle size and maintain particle size distribution during the subsequent formation of the "internal aqueous / oil phase" emulsion, a water-soluble polymer is added to the obtained internal aqueous phase as a "protective layer" for the particles. This water-soluble polymer adsorbs onto the particle surface during the subsequent formation of the "internal aqueous / oil phase" emulsion, forming a surface layer of a certain thickness, which effectively hinders collisions and aggregation between particles, further improving the stability of the system. Next, the second active metal is dispersed in water containing a hydrophilic agent in ionic form to obtain the external aqueous phase. Then, under specific conditions, the above-mentioned "internal aqueous / oil phase" emulsion is further dispersed in the external aqueous phase to finally obtain the hydrogenation catalyst impregnation solution.
[0087] The present invention employs an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal. Utilizing the high dispersion of the inner aqueous phase in the oil phase and the high dispersion of the "inner aqueous phase / oil phase" in the outer aqueous phase, the inner aqueous phase serves as the carrier matrix for the first active metal, while the outer aqueous phase serves as the carrier matrix for the second active metal. The oil phase then loads and isolates the metals in the inner and outer aqueous phases. Combined with other steps of the present invention, the final residue oil hydrodemetallization catalyst exhibits significantly improved activity and stability. Detailed Implementation
[0088] The technical solutions and effects of the present invention will be further illustrated below with reference to the embodiments, but the invention is not limited to the following embodiments.
[0089] In this invention, the pore structure and specific surface area of the catalyst are characterized using the Mack ASAP-2420 physical adsorption instrument.
[0090] Unless otherwise specified, all experimental materials used in this invention were purchased from conventional biochemical reagent manufacturers.
[0091] Example 1
[0092] Preparation of Ni-modified activated carbon support:
[0093] (I) 48.6 g of the first active metal nickel (nickel nitrate), 36.0 g of the dispersing agent silica sol (the silica sol contains 30% silica by mass) and 376.0 g of water were used to prepare an impregnation solution (the nickel content as oxide was 2.67% by mass and the dispersing agent as silica by mass was 2.34%). 297.0 g of high-temperature activated carbon (heat resistance temperature of 800℃ and particle size of 3.0 μm) was saturated and impregnated. After impregnation, the carbon was dried at 150℃ for 4 h and calcined at 650℃ for 3 h to obtain the Ni-modified activated carbon precursor.
[0094] (II) The Ni-modified activated carbon precursor obtained above was mixed with 6.5g of alkaline additive (NaOH), ground (particle size after grinding was 5.0μm), and dried at 140℃ for 5h to obtain the Ni-modified activated carbon carrier.
[0095] Preparation of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0096] In this example, the surfactant is glyceryl distearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:7.0. The co-emulsifier is octadecyl alcohol, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 20:278:58.5:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.6. The mass ratio of nickel source (oxidant:hydrophilic agent:water) is 9.1:32:400. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 0.8:1.0.
[0097] (a) Add the surfactant glyceryl distearate to the silicone oil, heat to 80°C, and wait for the silicone oil to melt to obtain the oil phase;
[0098] (b) Add the co-emulsifier octadecanol, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is raised to 120°C, the temperature is maintained for 4 hours. The stirring speed is kept constant until a clear solution is obtained.
[0099] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0100] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0101] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0102] (f) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (d) to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0103] Catalyst preparation:
[0104] 364.6 g of boehmite (alumina content of 72.0%), 150.0 g of the Ni-modified activated carbon carrier obtained above, 5.47 g of nitric acid, 8.0 g of guar gum powder, and 360.0 g of deionized water were mixed and kneaded, then extruded into a four-leaf clover shape, dried at 150°C for 5 h, and calcined at 700°C for 4 h to obtain a composite carrier.
[0105] The obtained composite carrier was mixed evenly with an aqueous emulsion containing polyfurfuryl alcohol and hydroxypropyl methylcellulose, dried at 160°C for 4 hours, and then calcined at 700°C for 4 hours under a nitrogen atmosphere to obtain the modified composite carrier. The aqueous emulsion contained 12.0% polyfurfuryl alcohol and 2.5% hydroxypropyl methylcellulose by mass. The ratio of aqueous emulsion (volume in mL) to composite carrier (volume in g) was 1.3 mL / g.
[0106] The modified composite carrier was impregnated with the above-obtained "inner aqueous phase / oil phase / outer aqueous phase" impregnation solution containing the second active metal by saturation impregnation. After standing for 24 hours, it was dried at 120℃ for 6 hours and then calcined in two stages (the first stage calcination temperature was 450℃, the calcination time was 4 hours, and the calcination atmosphere was air; the second stage calcination temperature was 600℃, the calcination time was 6 hours, and the calcination atmosphere was nitrogen) to obtain the hydrogenation demetallization catalyst CAT-1.
[0107] Example 2
[0108] Preparation of Ni-modified activated carbon support:
[0109] (I) 145.8 g of the first active metal nickel (nickel nitrate), 112.0 g of dispersant (silica sol with a mass content of 30% by mass) and 376.0 g of water were used to prepare an impregnation solution (nickel with a mass content of 5.82% by mass based on oxides and dispersant with a mass content of 5.30% by mass based on silica). 297.0 g of high-temperature activated carbon (same as in Example 1) was saturated with the solution. After impregnation, the solution was dried at 160 °C for 4 h and calcined at 700 °C for 3 h to obtain the Ni-modified activated carbon precursor.
[0110] (II) The Ni-modified activated carbon precursor obtained above was mixed with 8.5g of alkaline additive (NaOH), ground (particle size after grinding was 5.0μm), and dried at 120℃ for 6h to obtain the Ni-modified activated carbon carrier.
[0111] Preparation of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0112] In this example, the surfactant is glyceryl distearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:7.0. The co-emulsifier is octadecyl alcohol, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 20:278:58.5:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.6. The mass ratio of nickel source (oxidant:hydrophilic agent:water) is 3.8:32:400. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 0.8:1.0.
[0113] (a) Add the surfactant glyceryl distearate to the silicone oil, heat to 80°C, and wait for the silicone oil to melt to obtain the oil phase;
[0114] (b) Add the co-emulsifier octadecanol, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is raised to 120°C, the temperature is maintained for 4 hours. The stirring speed is kept constant until a clear solution is obtained.
[0115] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0116] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0117] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0118] (f) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (d) to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0119] Catalyst preparation:
[0120] 364.6 g of boehmite (alumina content of 72.0%), 106.0 g of the Ni-modified activated carbon carrier obtained above, 5.47 g of nitric acid, 8.0 g of guar gum powder, and 360.0 g of deionized water were mixed and kneaded, then extruded into a four-leaf clover shape, dried at 150°C for 5 h, and calcined at 700°C for 4 h to obtain a composite carrier.
[0121] The obtained composite carrier was mixed evenly with an aqueous emulsion containing polyfurfuryl alcohol and hydroxypropyl methylcellulose, dried at 160°C for 4 hours, and then calcined at 700°C for 4 hours under a nitrogen atmosphere to obtain the modified composite carrier. The aqueous emulsion contained 12.0% polyfurfuryl alcohol and 2.5% hydroxypropyl methylcellulose by mass. The ratio of aqueous emulsion (volume in mL) to composite carrier (volume in g) was 1.3 mL / g.
[0122] The modified composite carrier was impregnated with the above-obtained "inner aqueous phase / oil phase / outer aqueous phase" impregnation solution containing the second active metal by saturation impregnation. After standing for 24 hours, it was dried at 120℃ for 6 hours and then calcined in two stages (the first stage calcination temperature was 450℃, the calcination time was 4 hours, and the calcination atmosphere was air; the second stage calcination temperature was 600℃, the calcination time was 6 hours, and the calcination atmosphere was nitrogen) to obtain the hydrogenation demetallization catalyst CAT-2.
[0123] Example 3
[0124] In this example, the Ni-modified activated carbon carrier is the same as in Example 1.
[0125] In this example, the preparation of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal is as follows:
[0126] The surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the surfactant to silicone oil mass ratio is 1.0:4.0. The co-emulsifier is propylene glycol, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 20:278:58.2:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:5.0. The mass ratio of nickel source (oxidant:hydrophilic agent:water) is 224:32:400. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 6.0:1.0.
[0127] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 80°C, and wait for the silicone oil to melt to obtain the oil phase;
[0128] (b) Add the co-emulsifier propylene glycol, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is heated to 120°C, the temperature is maintained for 4 hours. The stirring speed is kept constant until a clear solution is obtained.
[0129] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0130] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0131] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0132] (f) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (d) to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0133] In this example, the catalyst was prepared according to the method in Example 1, and the final hydrogenation demetallization catalyst CAT-3 was obtained.
[0134] Example 4
[0135] In this example, the Ni-modified activated carbon carrier is the same as in Example 1.
[0136] In this example, the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal is the same as in Example 1.
[0137] In this example, the preparation of the catalyst:
[0138] 364.6 g of boehmite (alumina content of 72.0%), 150.0 g of the Ni-modified activated carbon carrier obtained above, 5.47 g of nitric acid, 8.0 g of guar gum powder, and 360.0 g of deionized water were mixed and kneaded, then extruded into a four-leaf clover shape, dried at 150°C for 5 h, and calcined at 700°C for 4 h to obtain a composite carrier.
[0139] The obtained composite carrier was mixed evenly with an aqueous emulsion containing phenolic resin and hydroxypropyl cellulose, dried at 140℃ for 6 h, and then calcined at 650℃ for 3 h under a nitrogen atmosphere to obtain the modified composite carrier. The aqueous emulsion contained 10.0% phenolic resin and 2.0% hydroxypropyl methylcellulose by mass. The ratio of aqueous emulsion (by volume mL) to composite carrier (by mass g) was 1.2 mL / g.
[0140] The modified composite carrier was impregnated with the above-obtained "inner aqueous phase / oil phase / outer aqueous phase" impregnation solution containing the second active metal by saturation impregnation. After standing for 24 hours, it was dried at 120℃ for 6 hours and then calcined in two stages (the first stage calcination temperature was 400℃, the calcination time was 3 hours, and the calcination atmosphere was air; the second stage calcination temperature was 650℃, the calcination time was 4 hours, and the calcination atmosphere was nitrogen) to obtain the hydrogenation demetallization catalyst CAT-4.
[0141] Comparative Example 1
[0142] Compared to Example 1, the difference lies in the fact that no alkaline additive is introduced in step (II) of preparing the Ni-modified activated carbon support. The final hydrogenation demetallization catalyst DCAT-1 was obtained.
[0143] Comparative Example 2
[0144] Compared to Example 1, the difference lies in that the composite support is not subjected to surface carbonization treatment during catalyst preparation. Instead, it is directly impregnated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal. The final hydrogenation demetallization catalyst DCAT-2 was obtained.
[0145] Comparative Example 3
[0146] Compared to Example 1, the difference lies in the solution used in the carbon coating process during catalyst preparation, which is replaced with a 12.0% (w / w) glucose aqueous solution. The ratio of glucose aqueous solution (volume in mL) to composite support (volume in g) is 1.2 mL / g. The final hydrogenation demetallization catalyst DCAT-3 was obtained.
[0147] Comparative Example 4
[0148] Compared to Example 1, the difference lies in that the first active metal Ni is not added in the preparation of the modified activated carbon support; the amount of MoO3 introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal is 100% of the total MoO3 loading in the catalyst; and the amount of NiO introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal is 100% of the total NiO loading in the catalyst. The final hydrogenation demetallization catalyst DCAT-4 is thus obtained.
[0149] Comparative Example 5
[0150] Compared to Example 1, the difference lies in that no water-soluble polymer is introduced during the preparation of the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal. The final hydrogenation demetallization catalyst DCAT-5 was obtained.
[0151] Comparative Example 6
[0152] The difference compared to Example 1 is that the preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is as follows:
[0153] In this example, the surfactant is glyceryl distearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:7.0. The co-emulsifier is octadecyl alcohol, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 20:278:58.5:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.6. The mass ratio of nickel source (oxidant:hydrophilic agent:water) is 9.1:32:400. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 0.8:1.0.
[0154] (a) Molybdenum oxide, phosphoric acid, and water-soluble polymer were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 500 r / min. When the temperature was raised to 120°C, it was maintained for 4 hours. A constant stirring speed was maintained until a transparent and clear solution was obtained, thus obtaining the internal aqueous phase.
[0155] (b) Add basic nickel carbonate and a hydrophilic agent to water to obtain an external aqueous phase;
[0156] (c) The surfactant, silicone oil, and co-emulsifier are added to the aqueous phase obtained in step (a) while stirring. The shear homogenization rate is 15,000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion state, an "aqueous phase / oil phase" type emulsion is obtained.
[0157] (d) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (c) to the outer aqueous phase obtained in step (b) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0158] The hydrogenation demetallization catalyst DCAT-6 was finally prepared.
[0159] Comparative Example 7
[0160] Compared with Example 1, the difference lies in that the calcination process after impregnation of the modified composite support does not use a mixed atmosphere; the calcination temperature is 550℃, the calcination time is 6 hours, and the calcination atmosphere is air. The final hydrogenation demetallization catalyst DCAT-7 was obtained.
[0161] Table 1. Physicochemical properties and catalyst composition of each example of hydrodemetallization catalyst.
[0162] Serial Number Example 1 Example 2 Example 3 Example 4 Catalyst number CAT-1 CAT-2 CAT-3 CAT-4 <![CDATA[Specific surface area, m 2 / g]]> 163 165 166 161 <![CDATA[pore volume, cm 3 / g]]> 0.82 0.83 0.84 0.78 First active metal NiO, wt% 1.08 2.83 1.09 1.05 Second active metal <![CDATA[MoO3,wt%]]> 14.75 14.72 14.73 14.70 NiO, wt% 3.02 1.27 3.01 3.04 <![CDATA[P2O5,wt%]]> 3.10 3.08 3.12 3.07 Alumina: Activated Carbon 2.0∶1 3.1∶1 2.0∶1 2.0∶1
[0163] Table 2 Physicochemical properties and catalyst composition of each comparative example of hydrogenation demetallization catalyst
[0164]
[0165] Evaluation test
[0166] Activity stability tests were conducted on Examples 1-4 and Comparative Examples 1-7 using a 200mL fixed-bed hydrogenation test apparatus. The feedstock was residue oil with a density of 984.8 kg / m³. 3 (20℃), S content 2.55wt%, Ni and V contents 27.6μg / g and 56.7μg / g respectively, CCR content 11.9wt%, the demetallization rate after 2000h of operation in Example 1 was 100%, and all others were relative demetallization rates. Specific experimental conditions are shown in Table 3, and experimental results are shown in Tables 4 and 5.
[0167] Table 3 Experimental conditions
[0168] Reaction temperature, °C 380 Reaction pressure, MPa 15.7 <![CDATA[Liquid hourly volume space velocity, h -1 > 1.0 Hydrogen-to-oil ratio, V / V 800
[0169] Table 4. Test results of the hydrogenation demetallization catalysts in each example.
[0170]
[0171]
[0172] Table 5. Experimental results of hydrogenation demetallization catalysts in each comparative example.
[0173]
[0174] As can be seen from Tables 1-5, the hydrodemetallization catalyst prepared according to the method of the present invention has a high specific surface area and pore volume, as well as high hydrogenation activity and stability, and can well meet the requirements of the hydrodemetallization process of heavy and residual oils.
Claims
1. A method for preparing a hydrogenation demetallization catalyst, comprising the following steps: (1) Preparation of activated carbon carrier modified with the first active metal; (2) The activated carbon carrier modified with the first active metal obtained in step (1) is mixed with boehmite and adhesive, molded, and calcined to obtain a composite carrier; (3) The composite carrier obtained in step (2) is subjected to surface carbon coating treatment and calcined to obtain the modified composite carrier. (4) The modified composite support obtained in step (3) is impregnated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal, and then calcined to obtain the hydrogenation demetallization catalyst.
2. The preparation method according to claim 1, characterized in that, In step (1), the preparation method of the first active metal modified activated carbon support includes: (I) Activated carbon is impregnated with a first active metal impregnation solution containing a dispersing aid and then calcined to obtain a first active metal modified activated carbon precursor; (II) The first active metal modified activated carbon precursor obtained in step (I) is mixed with an alkaline additive, ground and dried to obtain the first active metal modified activated carbon carrier.
3. The preparation method according to claim 2, characterized in that, In step (I), the dispersing agent is silica sol; preferably, the silica sol has a silica content of 20.0% to 50.0% by mass.
4. The preparation method according to claim 2, characterized in that, In step (I), the first active metal is at least one of Group VIII metals, preferably Ni and / or Co; preferably, in the first active metal impregnation solution containing the dispersing aid, the mass content of the first active metal, calculated as oxide, is 2.0% to 8.0%, and the mass content of the dispersing aid, calculated as silica, is 2.0% to 6.0%.
5. The preparation method according to claim 2, characterized in that, In step (I), the activated carbon is high-temperature activated carbon; preferably, the minimum heat resistance temperature of the high-temperature activated carbon is 750°C; and / or, the particle size of the activated carbon is 0.1 to 6.0 μm.
6. The preparation method according to claim 2, characterized in that, In step (I), the calcination conditions are: a temperature of 550–750°C, a time of 3–8 hours, and a calcination atmosphere of one or more of air, water vapor, and nitrogen.
7. The preparation method according to claim 2, characterized in that, In step (II), the alkaline additive is one or more of sodium hydroxide, potassium hydroxide, and sodium carboxylate; and / or, the mass ratio of the alkaline additive to the activated carbon used in step (I) is 0.01 to 0.
10.
8. The preparation method according to claim 1, characterized in that, In step (2), the alumina content in the pseudoboehmite is 65.0% to 80.0% by mass; And / or, the adhesive is an inorganic acid and / or an organic acid, wherein the inorganic acid is one or more of nitric acid, sulfuric acid, boric acid, and phosphoric acid, and the organic acid is one or more of tartaric acid, citric acid, and oxalic acid; And / or, the mass of the adhesive is 0.5% to 5.0% of the total mass of the pseudoboehmite (calculated as alumina) and the activated carbon carrier modified with the first active metal.
9. The preparation method according to claim 1, characterized in that, In step (2), the roasting process adopts programmed heating with a heating rate of 1℃ / min to 3℃ / min, a roasting temperature of 550℃ to 750℃, a roasting time of 2 to 8 hours, and a roasting atmosphere of one or more of air, nitrogen, or water vapor, preferably air.
10. The preparation method according to claim 1, characterized in that, In step (3), the carbon coating treatment preferably uses an aqueous emulsion containing a polymer compound and water-soluble cellulose; the polymer compound is one or more of polyimide, polyfurfuryl alcohol, phenolic resin, etc.; the water-soluble cellulose is one or more of hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose. And / or, in the aqueous emulsion, the mass content of the polymer compound is 8.0% to 16.0%, and the mass content of the water-soluble cellulose is 0.5% to 3.5%; And / or, the ratio of the volume of the aqueous emulsion (mL) to the mass of the composite carrier (g) is 0.8–1.5 mL / g.
11. The preparation method according to claim 1, characterized in that, In step (3), the calcination conditions are: calcination temperature of 500-700℃, calcination time of 2.0-8.0h, and calcination atmosphere of inert atmosphere, wherein the inert atmosphere is one or more of nitrogen and argon. And / or, in step (4), the roasting adopts a two-stage roasting process. The first stage roasting temperature is 350-450℃, the roasting time is 2-6h, and the roasting atmosphere is one or more of air, nitrogen, or water vapor, preferably air; the second stage roasting temperature is 450-750℃, the roasting time is 2-8h, and the roasting atmosphere is one or more of air, nitrogen, or water vapor, preferably nitrogen; preferably, the second stage roasting temperature is 150-250℃ higher than the first stage roasting temperature.
12. The preparation method according to claim 1, characterized in that, In step (4), the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal includes an inner aqueous phase, an oil phase covering the inner aqueous phase, and an outer aqueous phase; And / or, the inner aqueous phase includes a Group VIB metal source, a co-emulsifier, a water-soluble polymer, water, and optional auxiliary agent sources; the outer aqueous phase includes a Group VIII metal source, a hydrophilic agent, and water; and the oil phase includes a surfactant and oil.
13. The preparation method according to claim 12, characterized in that, The mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0; And / or, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0; And / or, the mass ratio of the "internal aqueous phase / oil phase" to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.
0.
14. The preparation method according to claim 12, characterized in that, The Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co; the additive is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus; And / or, the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate; And / or, the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol and glycerin; And / or, the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide; And / or, the surfactant is selected from one or more of glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol; And / or, the oil is selected from at least one of silicone oil and vegetable oil; the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil; and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
15. The preparation method according to claim 12, characterized in that, In the internal aqueous phase, the mass concentration of water-soluble polymer is 4.0% to 14.0%; And / or, in the internal aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; the concentration of additives as oxides is 0-12.0 g / 100 mL, preferably 0.5-12.0 g / 100 mL. And / or, in the internal aqueous phase, the mass concentration of the co-emulsifier is 0.5% to 5.0%.
16. The preparation method according to claim 12, characterized in that, In the external aqueous phase, the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL; And / or, in the external aqueous phase, the mass concentration of the hydrophilic agent is 4.0% to 15.0%.
17. The preparation method according to claim 1 or 12, characterized in that, In step (4), the preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal includes: (a) The surfactant and oil are mixed and heated to obtain the oil phase; (b) Mix the co-emulsifier, the Group VIB metal source, water and optional auxiliary source, and heat to obtain a clear solution; (c) Add a water-soluble polymer to the clear solution obtained in step (b) to obtain an internal aqueous phase; (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a) while the oil phase remains liquid during the dropwise addition. Simultaneously, stirring and shearing are performed to homogenize the mixture, resulting in an "aqueous phase / oil phase" emulsion. (e) Mixing a Group VIII metal source with water containing a hydrophilic agent to obtain an external aqueous phase; (f) The "inner aqueous phase / oil phase" type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (e) to obtain an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution.
18. The preparation method according to claim 17, characterized in that, In step (a), the heating temperature is 45–85°C; And / or, in step (b), the heating to a temperature of 90–120°C; And / or, in step (d), the stirring-shear homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a shear homogenization time of 3 to 8 min, and a shear homogenization temperature of 50 to 85°C.
19. The hydrogenation demetallization catalyst prepared by any one of the preparation methods described in claims 1-18.
20. The catalyst according to claim 19, characterized in that, The catalyst includes a support containing a first active metal and a second active metal. The support containing the first active metal includes alumina, activated carbon, and the first active metal. The mass ratio of alumina to activated carbon is 1.0 to 4.0:1, preferably 1.5 to 3.5:
1.
21. The catalyst according to claim 19, characterized in that, The first active metal is at least one of Group VIII metals, preferably Ni and / or Co; the second active metal includes at least one of Group VIB metals and at least one of Group VIII metals, wherein the Group VIB metal is preferably Mo and / or W, and the Group VIII metal is preferably Ni and / or Co.
22. The catalyst according to claim 19, characterized in that, In the catalyst, based on the mass of the catalyst, the content of group VIB metal oxides is 12.0% to 20.0%, and the content of group VIII metal oxides is 2.0% to 8.0%. Preferably, in the catalyst, the content of Group VIII metals in the first active metal, calculated as oxides, is 20.0% to 45.0% of the total Group VIII metals in the catalyst, calculated as oxides, and the content of Group VIII metals in the second active metal, calculated as oxides, is 55.0% to 80.0% of the total Group VIII metals in the catalyst, calculated as oxides.
23. The catalyst according to claim 19, characterized in that, The catalyst includes an additive selected from at least one of phosphorus, silicon, or boron, preferably phosphorus; Preferably, in the catalyst, the content of the auxiliary agent, calculated as oxide, is 2.0% to 5.0% based on the mass of the catalyst.
24. The catalyst according to claim 19, characterized in that, The catalyst has a specific surface area of 150–180 m². 2 / g, with a pore volume of 0.70-0.95mL / g; preferably, the catalyst has a specific surface area of 155-170m² / g and a pore volume of 0.75-0.90mL / g.
25. The application of the hydrodemetallization catalyst prepared by any of the preparation methods of claims 1-18 or any of the catalysts of claims 19-24 in the hydrotreating of heavy oil and residual oil.
Citation Information
Patent Citations
Preparation method of residuum hydrodemetallization catalyst
CN105709765A
